Passos/Santa Comba Mountain in the context of the late prehistory of northern Portugal - Sanches, Maria de Jesus (1996)
This paper summarizes the results of archaeological work carried out during the past eight years on the Passos/Santa Comba Mountain in northern Portugal. The more important sites there are thirteen painted rock shelters. One of them, Buraco da Pala, was occupied for three millennia, making it reasonable to assume that it played a part in different social, economic and symbolic systems. It was used for settlement purposes between the late sixth/early fifth millennium BC and the beginning of the third. A high number of burnt cereal grains shows the introduction of farming in the interior of northern Portugal. Buraco da Pala was used as a granary and storage was carried out in large pottery vessels that occupied most of the usable space in the shelter. These levels provide evidence both for the intensification of agricultural production in this area during the Chalcolithic period and for different ways of symbolically appropriating the surrounding territory.